Graphite rapidly forms via annihilation of screw dislocations - Martin, Jacob; Fogg, Jacob; Francas, Gabriel; Putman, Kate; Turner, Ethan; Suarez-Martinez, Irene; Marks, Nigel (2023)
Graphite is the thermodynamically stable form of carbon and yet is remarkably difficult to synthesize. We show the annihilation of screw dislocations is critical for graphitization. These dislocations wind through the layers like a spiral staircase, inhibiting lateral growth of the graphenic crystallites (La) and preventing AB stacking of Bernal graphite. High-resolution transmission electron microscopy identifies screws as interdigitated fringes with narrow focal depth in graphitizing polyvinyl chloride. Molecular dynamics simulations of parallel graphenic fragments confirm that screws spontaneously form during heating, with higher annealing temperature driving screw annihilation and crystallite growth. The time evolution and kinetics of graphitization is tracked via X-ray diffraction, showing the growth of La and reduction of the interlayer spacing, consistent with screw annihilation. We find that graphite forms orders of magnitude faster than previously assumed, taking less than ten seconds at 3000 °C and just minutes at 2500 °C. This rapid transformation suggests major cost savings in synthetic graphite production, important for lithium-ion batteries and smelting electrodes. By reducing the time spent at ultra-high temperatures, energy costs and component degradation can be significantly lower.